Public Finance in the Era of the Covid-19 Crisis - David R. Agrawal; Aline Bütikofer (Center for Economic Studies and ifo Institute (CESifo), 2022)
The COVID-19 crisis poses new policy challenges and has spurred new research agendas in public economics. In this article, we selectively reflect on how the field of public economics has been shaped by the COVID-19 pandemic and discuss several areas where more research is necessary. We highlight major changes and inequalities in the labor market and K-12 education, in addition to discussing how technological change creates new challenges for the taxation of income and consumption. We discuss various policy responses to these challenges and the role of fiscal federalism in the context of worldwide crises. Finally, we summarize the key issues discussed at the 2021 International Institute of Public Finance Congress and the papers published in this special issue.
Keywords: H00; J00; 330; public economics; labor economics; education; tax; expenditure; Covid-19; inequality; fiscal federalism